The Role Of The Internal Control System In Encouraging The Sustainable Financial Performance Of MSMEs - Victor Amanusa Talakua; Albertus Lalaun (STEBIS Bina Mandiri, 2026)
This study aims to analyze the role of internal control systems in improving the financial performance of sustainable Micro, Small, and Medium Enterprises (MSMEs). The research method used is a quantitative, associative approach. The population in this study consists of MSME actors in Ambon City, and the sampling technique is purposive. Data were collected through questionnaires and analyzed using simple linear regression. The results show that the internal control system has a positive and significant effect on the financial performance of MSMEs. This indicates that the better the implementation of the internal control system, the higher the financial performance achieved. In addition, the internal control system also plays a role in improving operational efficiency, minimizing errors, and supporting business sustainability. Therefore, the implementation of an effective internal control system is an important factor in enhancing financial performance and ensuring the long-term sustainability of MSMEs.